2008
DOI: 10.1051/medsci/2008242s184
|View full text |Cite
|
Sign up to set email alerts
|

Couple et sexualité des femmes d'Afrique sub-saharienne vivant avec le VIH/sida en France

Abstract: RésuméEn France, l'épidémie de sida concerne une part croissante de femmes originaires d'Afrique sub-saharienne. À partir d'entretiens réalisés auprès de 32 femmes, cet article analyse l'impact du diagnostic sur les relations de couple, la sexualité et les projets reproductifs. Les femmes interviewées ayant des parcours biographiques et migratoires diversifiés, les répercussions de l'annonce de la séropositivité sont variées. Pour les jeunes femmes en couple, la découverte de la séropositivité peut être suivie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
3
0
8
Order By: Relevance
“…In Burkina Faso, an analysis of the effects of gender on testing showed that while fear of rejection by partners, friends or family members was cited as a reason for not using testing in general, women also cited a fear of losing their livelihoods ( 37 ). A woman's precariousness and/or financial dependence is a factor that reinforces her vulnerability to the undesirable effects of sharing HIV status within the couple ( 38 ). For this reason, a study conducted in Mali as part of the Gundo-So program emphasized the need to strengthen programs supporting PLHIV and empower PLHIV so that they can make free and informed decisions regarding the disclosure of their HIV status ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Burkina Faso, an analysis of the effects of gender on testing showed that while fear of rejection by partners, friends or family members was cited as a reason for not using testing in general, women also cited a fear of losing their livelihoods ( 37 ). A woman's precariousness and/or financial dependence is a factor that reinforces her vulnerability to the undesirable effects of sharing HIV status within the couple ( 38 ). For this reason, a study conducted in Mali as part of the Gundo-So program emphasized the need to strengthen programs supporting PLHIV and empower PLHIV so that they can make free and informed decisions regarding the disclosure of their HIV status ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…En France, les recherches en sciences sociales sur la santé des migrants se multiplient. Elles interrogent plusieurs problématiques : les inégalités de santé [1,2,3], l'accès au dépistage et aux soins [4,5,6], l'articulation des parcours de maladie et de migration [7,8,9], les enjeux politiques de la santé des étrangers [10,11,12]. Les attentes des patients migrants vis-à-vis du médecin en contexte de maladie chronique restent peu explorées, de même que les caractéristiques de la relation médecin-patient [13].…”
Section: Introductionunclassified
“…Most were young women who had come to France on their own. They had learned of 7 This was post-doctoral research conducted-at Inse~Ij research unit 569, and was funded by Sidaction and the Fondation de France (see also Pourette 2006Pourette , 2008aPourette , 2008b. 8 The recruitrnent criteria were as follows: over 18 years of age, born in a country of Sub-Saharan Africa, having been living in Fran~e for at least a year and having been diagnosed as mY-positive at least a year before the date of the survey.…”
Section: The Surveymentioning
confidence: 99%